Letter (copy) : Deputation to the Archbishop of Westminster - Citrine, Walter, 1887-1983
011-0147-001 /12. WMC/HVT/FC/543. Secretary's. 11th February, 1937. Mr. L. J. Duffy, Secretary, The Labour Party, 21, Molesworth Street, DUBLIN, C.2. Dear Mr. Duffy, Deputation to the Archbishop of Westminster Referring to your letter of the 5th instant in regard to the above matter I understand tnat Mr. Middleton of the Labour Party was received a similar letter. The deputation in question was entirely unofficial, but I have secured some particulars which have been passed to Mr. Middleton and I understand that he is replying to you in greater detail. Yours sincerely, General Secretary. 292/946/11/147